2016
DOI: 10.1002/ece3.1950
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and iridescent feather reflectance data reveal recent genetic diversification and phenotypic differentiation in a cloud forest hummingbird

Abstract: The present day distribution and spatial genetic diversity of Mesoamerican biota reflects a long history of responses to habitat change. The hummingbird Lampornis amethystinus is distributed in northern Mesoamerica, with geographically disjunct populations. Based on sampling across the species range using mitochondrial DNA (mtDNA) sequences and nuclear microsatellites jointly analysed with phenotypic and climatic data, we (1) test whether the fragmented distribution is correlated with main evolutionary lineage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 117 publications
(224 reference statements)
1
6
0
Order By: Relevance
“…This pattern of high genetic differentiation is congruent with other studies of Mesoamerican vertebrate species ( Barber, 1999 ; Zarza, Reynoso & Emerson, 2008 ; Bonaccorso, 2009 ; Bryson et al, 2011 ; Smith et al, 2011 ; Arbeláez-Cortés, Roldán-Piña & Navarro-Sigüenza, 2014 ; Castañeda Rico et al, 2014 ). In Trochilidae, high levels of geographic structure have been previously reported, related to differences in current or historical ecological conditions ( Adelomyia melanogenys : Chaves et al, 2007 ; Lampornis amethystinus : Cortés-Rodríguez et al, 2008 ; Ornelas et al, 2016 ). Also, moderate levels of differentiation have been found in hummingbird species co-distributed in Mesoamerican cloud forests ( Campylopterus curvipennis : González, Ornelas & Gutiérrez-Rodríguez, 2011 ; Amazilia cyanocephala : Rodríguez-Gómez, Gutiérrez-Rodríguez & Ornelas, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This pattern of high genetic differentiation is congruent with other studies of Mesoamerican vertebrate species ( Barber, 1999 ; Zarza, Reynoso & Emerson, 2008 ; Bonaccorso, 2009 ; Bryson et al, 2011 ; Smith et al, 2011 ; Arbeláez-Cortés, Roldán-Piña & Navarro-Sigüenza, 2014 ; Castañeda Rico et al, 2014 ). In Trochilidae, high levels of geographic structure have been previously reported, related to differences in current or historical ecological conditions ( Adelomyia melanogenys : Chaves et al, 2007 ; Lampornis amethystinus : Cortés-Rodríguez et al, 2008 ; Ornelas et al, 2016 ). Also, moderate levels of differentiation have been found in hummingbird species co-distributed in Mesoamerican cloud forests ( Campylopterus curvipennis : González, Ornelas & Gutiérrez-Rodríguez, 2011 ; Amazilia cyanocephala : Rodríguez-Gómez, Gutiérrez-Rodríguez & Ornelas, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the well-known movement abilities of Trochilidae species, some studies have found that geographical barriers are crucial in promoting high levels of differentiation and the diversification of independent evolutionary lineages in various regions, such as the Andes region (e.g., Adelomyia melanogenys , Chaves & Smith, 2011 ), Mesoamerica ( Ornelas et al, 2016 ), the Motagua fault region ( Rodríguez-Gómez & Ornelas, 2014 ), and the Isthmus of Tehuantepec ( Cortés-Rodríguez et al, 2008 ; González, Ornelas & Gutiérrez-Rodríguez, 2011 ). In contrast, in lowland Neotropical birds, high levels of intraspecific diversification are better explained by the hypothesis of limited dispersal ability ( Burney & Brumfield, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…This population decrease, followed by rapid population growth and range expansion is coincident with the Last Glacial Maximum during the Late Pleistocene (~21,000 ya), when colder conditions may have allowed the formation of corridors between previously isolated humid montane forest patches (Figure 4a), likely enhanced by the downward altitudinal range changes of the forest belt (Hooghiemstra et al 2006, Gutiérrez-Rodríguez et al 2011, Rojas-Soto et al 2012, Ornelas et al 2010, 2013, Ramírez-Barahona and Eguiarte 2013). Such a scenario, probably promoted gene flow between previously isolated populations (e. g., Hewitt 2000, Zink and Blackwell-Rago 2000, Weir 2006, Hooghiemstra et al 2006, Barber and Klicka 2010, Pérez-Emán et al 2010, Wachowiak et al 2013, Bagley and Johnson 2014, Ornelas et al 2016). In addition, an interesting result emerging from our ENM is that regions inhabited by yellow-plumaged and grey-plumaged populations in Chiapas-Guatemala have apparently never been isolated, which seems to support conclusions by Paynter (1972, 1978) regarding the weakness of a low river valley as an effective barrier in separating these populations.…”
Section: Discussionmentioning
confidence: 99%
“…The first pattern has been found in hummingbirds (Trochilidae), with strong geographic structuring ( i ) in species with populations separated by biogeographic barriers such as the Isthmus of Tehuantepec, the Trans-Mexican Volcanic Belt, and/or the Motagua-Polochic-Jocotán fault system (Hernández-Soto et al, 2018; Jiménez & Ornelas, 2016; Malpica & Ornelas, 2014; Rodríguez-Gómez et al, 2013, 2021, Zamudio-Beltrán et al, 2020, 2020b); ( ii ) species with disjunct distribution of populations (Arbeláez-Cortés & Navarro-Sigüenza, 2013; González et al, 2011; Licona-Vera & Ornelas, 2014); ( iii ) or in species inhabiting naturally fragmented habitats such as cloud forests (Cortés-Rodríguez et al, 2008a; Ornelas et al, 2016; Zamudio-Beltrán & Hernández-Baños, 2018). In contrast, the second pattern of weak geographic structuring and high levels of gene flow has been found in hummingbird species inhabiting lowland humid forest edges and coastal habitats, oases in tropical deciduous forests and arid montane scrub (González-Rubio et al, 2016; Licona-Vera et al, 2018a; Miller et al, 2011; Rodríguez-Gómez & Ornelas, 2015, 2018).…”
Section: Introductionmentioning
confidence: 99%